Understanding the Polar Character Trend in a Series of Diels-Alder Reactions Using Molecular Quantum Similarity and Chemical Reactivity Descriptors. (7th July 2014) - Morales-Bayuelo, Alejandro; Vivas-Reyes, Ricardo
Abstract : In molecular similarity there is a premise " similar molecules tend to behave similarly "; however in the actual quantum similarity field there is no clear methodology to describe the similarity in chemical reactivity, and with this end an analysis of charge-transfer (CT) processes in a series of Diels-Alder (DA) reactions between cyclopentadiene (Cp) and cyano substitutions on ethylene has been studied. The CT analysis is performed in the reagent assuming a grand canonical ensemble and the considerations for an electrophilic system using B3LYP/6-31G ( d ) and M06-2X/6-311 +G ( d, p ) methods. An analysis for CT was performed in agreement with the experimental results with a good statistical correlation( R 2 = 0.9118 ) relating the polar character to the bond force constants in DA reactions. The quantum distortion analysis on the transition states (TS) was performed using molecular quantum similarity indexes of overlap and coulomb showing good correlation( R 2 = 0.8330 ) between the rate constants and quantum similarity indexes. In this sense, an electronic reorganization based on molecular polarization in terms of CT is proposed; therefore, new interpretations on the electronic systematization of the DA reactions are presented, taking into account that today such electronic systematization is an open problem in organic physical chemistry. Additionally, one way to quantify the similarity in chemical reactivity was shown, taking into account the dependence of the molecular alignment on properties when their position changes; in this sense a possible way to quantify the similarity of the CT in systematic form on these DA cycloadditions was shown.